Pemanfaatan Pangan Lokal untuk Pencegahan Anemia pada Remaja Putri di SMAS Adhyaksa 1 Kota Jambi - Nurita, Suci Rahmani; Julaecha, Julaecha; Perwitasari, Tuhu; Kusuma , Ratu (Universitas Baiturrahim, 2025)
The World Health Organization (WHO) in 2013 stated that anemia is one of the health problems worldwide, especially in developing countries. As many as 30% of the world's population is estimated to suffer from anemia, especially adolescents and pregnant women. The prevalence of anemia in adolescents in the world ranges from 40% -88%. The 2018 Riskesdas report stated that the prevalence of anemia in Indonesia is around 22.2% in the age group ≥ 15 years. The prevalence of anemia in urban adolescent girls in Jambi Province is 9.0%. Anemia causes a decrease in reproductive health function, inhibits the development of intelligence, motor skills and mental which results in decreased learning achievement. If adolescent girls suffer from anemia from the start, it will be very dangerous for pregnancy and childbirth if they later marry and become mothers. One of the factors that influences the occurrence of anemia is iron deficiency. Foods that can increase the absorption of iron, especially non-heme iron, are vitamin C and certain sources of animal protein, such as meat and fish. Handling anemia with food ingredients is still rarely done even though it has great potential to prevent anemia, especially in adolescent girls. This study aims to determine the description of the use of local food to prevent anemia in adolescent girls. This research method is descriptive research with a cross-sectional approach. The population of this study were all female students at SMAS Adhyaksa 1 Jambi City with a sample of 31 people using the Slovin formula. Samples were taken using a simple random sampling technique. This study was conducted from October 2023 to August 2024 at SMAS Adhyaksa 1 Jambi. The results showed that almost half of the female adolescents often (1x/day) consume protein (41.9%), vegetables 3-6x/week (48.4%), fruits 3-6x/week (45.2%). More than half of the female adolescents never consume iron tablets (58.1%) and tea/coffee with meals (54.8%). A small number of female adolescents rarely consume milk (38.7%). Local foods for preventing anemia that are most widely consumed by female adolescents at SMAS Adhyaksa 1 are red meat (animal protein source), tempeh (vegetable protein source), spinach (vegetables) and oranges (fruits). It is hoped that schools can increase education about the use of local food to prevent anemia and for young women, they can increase their intake of diverse local food to prevent anemia from occurring early on.